Histoplasmosis: Epidemiology in Latin America (2011)
Histoplasmosis is a frequent health problem in Latin American countries, but the fact that it is not a reportable disease prevents reliable estimates of its real incidence and impact on public health. Epidemiologic and clinical data remain patchy in general, and in some countries the information available is very limited. Histoplasmosis has a significant public health impact in susceptible populations such as immunosuppressed individuals, in whom the disease is associated with poor outcomes. Limited availability of diagnostic tools in many regions of Latin America is an additional problem, as many patients are already severely ill by the time of the diagnosis. Efforts are therefore necessary to ensure early diagnosis and appropriate treatment, limit the severity of the disease manifestations, and reduce morbidity and mortality. This paper reviews important aspects of the epidemiology of histoplasmosis, the most clinically significant endemic mycosis in Latin America. © Springer Science+Business Media, LLC 2011.